A novel colonoscope with panoramic visualization detected more simulated polyps than conventional colonoscopy in a live swine model - Gluck, Nathan; Fishman, Sigal; Melhem, Alaa; Goldfarb, Sharon; Halpern, Zamir; Santo, Erwin (Endoscopy International Open, 2015)
Background and study aims: The Aer-O-Scope™ Colonoscope System (AOS) combines panoramic 360° view with standard forward view. We assessed the AOS’s ability to identify lesions implanted in live swine, compared to conventional colonoscopy (CC).Patients and methods: Twelve swine colons were surgically ligated and beads sewn within. Five procedures (3 AOS and 2 CC) were performed on each swine and findings reported. Physicians were blinded to number, size, and color of beads. The sequence of procedures and physicians was randomized. Pigs, physicians, and colonoscopes were randomly alternated between examination rooms, maintaining physician blindness. Two independent blinded physicians interpreted procedure videos offline.Results: A total of 259 /273 (94.9 %) of lesions were visualized by AOS compared to 158 /182 with CC (86.8 %) (P = 0.002). Miss rates of lesions ≥ 6 mm were 2.6 % and 10.5 %, respectively (P = 0.022), and 6.9 % and 15.1 %, respectively, for lesions < 6 mm (P = 0.031). Mean agreement between AOS and CC for lesion detection was 88.3 %. The benefit of AOS was maintained in offline video review. Conclusions: AOS, featuring panoramic 360° view, demonstrated high detection rates for simulated colonic lesions in a live swine model.